Our Experience with Single Lung Ventilation in Thoracoscopic Paediatric Surgery - Bataineh, Z.A.; Zoeller, C.; Dingemann, C.; Osthaus, A.; Suempelmann, R.; Ure, B. (European Journal of Pediatric Surgery, 2012)
Introduction Data on the feasibility and effects of single lung ventilation (SLV) in children are scarce. We conducted a retrospective study on the feasibility of SLV during video-assisted thoracoscopic surgery (VATS) in children and adolescents undergoing major thoracic procedures.Methods A retrospective chart review of all records from patients who underwent VATS at our institution from 2000 to 2010 was done. Patients receiving SLV were analysed in detail. Endpoints of the analysis were conversion to open thoracotomy (frequency and reasons), postoperative duration of ventilation, and pulmonary complications such as radiologically confirmed atelectasis and pneumonia.Results 74 out of 305 patients (24%, 43 boys, 31 girls) with a mean age of 9.4 years (56 days–18 years) and mean weight of 34 kg (4.5–76 kg) had SLV. Lung resection was done in 43 (58%), pleural surgery in 17 (23%), a combination of both in 7 (9%), and mediastinal procedures in 7 (9%). 11 patients (15%) required conversion of VATS to open surgery, mostly because of problems with exposure of the operative field (73%). 32 patients (43%) were extubated immediately after the operation, whereas 8 (11%) required ventilation for more than 24 h. The mean intensive care unit stay was 1.6 days. 18 patients (24%) developed radiologically confirmed atelectasis, and 1 patient (1%) required bronchoscopic clearance. Pneumonia occurred in 1 case (1%) and was successfully treated with antibiotics.Conclusion SLV is feasible in children and adolescents undergoing VATS for a broad spectrum of procedures. However, despite SLV, the conversion rate in our series was 15%. The main reason for conversion was problems with exposure of the operative field. The complication rate for SLV was low. Atelectasis developed in every fourth patient but usually resolved spontaneously, and intervention to achieve ventilation was rarely indicated.
Keywords: single lung ventilation (SLV); video assisted thoracoscopic surgery (VATS); children